An Altar from the Castle Chapel of Atlit and its Journey to the Church of all Hallows by the Tower, London - Shotten-Hallel, Vardit (Palestine exploration quarterly, 2017)
An altar currently positioned in the columbarium of the Church of All Hallows by the Tower, London, was thought to have originated from the Templar castle of Atlit. However, lack of relevant documentation resulted in this being regarded as a myth rather than a genuine piece of history. To add confusion, a Maltese Cross, associated with the Hospitaller Order of St John, was carved on the front of the altar's table top-the mensa., Recently found documents reveal how this limestone altar was brought from the thirteenth-century Templar castle of Atlit and came into the possession of the church.